Asian capital market development and integration : challenges and opportunities - Asian Development Bank.; Korea Capital Market Institute (New Delhi : Oxford University Press, 2014)
Contributed articles.
"ADB, Korea Capital Market Institute."
Keywords: Capital market -- Asia -- 21st century